Dipyrrinato-Iridium(III) Complexes for Application in Photodynamic Therapy and Antimicrobial Photodynamic Inactivation - Senge, Mathias (My University, 2021)
The generation of bio-targetable photosensitizers is of utmost importance to the emerging field of photodynamic therapy and antimicrobial (photo-)therapy. A synthetic strategy is presented in which chelating dipyrrin moieties are used to enhance the known photoactivity of iridium(III) metal complexes. Formed complexes can thus be functionalized in a facile manner with a range of targeting groups at their chemically active reaction sites. Dipyrrins with N- and O-substituents afforded (dipy)iridium(III) complexes via complexation with the respective Cp*-iridium(III) and ppy-iridium(III) precursors (dipy=dipyrrinato, Cp*=pentamethyl-η5-cyclopentadienyl, ppy=2-phenylpyridyl). Similarly, electron-deficient [IrIII(dipy)(ppy)2] complexes could be used for post-functionalization, forming alkenyl, alkynyl and glyco-appended iridium(III) complexes. The phototoxic activity of these complexes has been assessed in cellular and bacterial assays with and without light; the [IrIII(Cl)(Cp*)(dipy)] complexes and the glyco-substituted iridium(III) complexes showing particular promise as photomedicine candidates. Representative crystal structures of the complexes are also presented.
Keywords: bio-targetable photosensitizers; Dipyrrins; phototoxic activity